2017
DOI: 10.1002/ijgo.12345
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fertility treatment on adverse perinatal outcomes in women aged at least 40 years

Abstract: Objective: To compare perinatal outcomes between spontaneous conception and assisted reproductive technologies (ART) among patients of advanced maternal age. Methods:The present retrospective study included data from singleton pregnancies of women aged at least 40 years who delivered between January 1, 1991, and December 31, 2013, at Soroka University Medical Center, Beer Sheva, Israel.Demographic, obstetric, and perinatal data were compared between pregnancies conceived with ART (in vitro fertilization [IVF] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
1
4
0
4
Order By: Relevance
“…In the present retrospective cohort study, we observed the increased risks of perinatal complications and poor neonatal outcomes related to ART, such as GDM, hypertension during pregnancy, ICP, placental abruption, premature rupture of membranes, postpartum hemorrhage, polyhydramnios, premature delivery, and low birth weight. Previous studies have reported that ART has an increased incidence of hypertension during pregnancy, GDM, ICP, postpartum hemorrhage, premature delivery, and low birth weight, [1316] which is consistent with our present results. The newest ART surveillance in USA reported 23.6% infants conceived with ART were born low birth weight and 29.9% of ART infants were preterm.…”
Section: Discussionsupporting
confidence: 93%
“…In the present retrospective cohort study, we observed the increased risks of perinatal complications and poor neonatal outcomes related to ART, such as GDM, hypertension during pregnancy, ICP, placental abruption, premature rupture of membranes, postpartum hemorrhage, polyhydramnios, premature delivery, and low birth weight. Previous studies have reported that ART has an increased incidence of hypertension during pregnancy, GDM, ICP, postpartum hemorrhage, premature delivery, and low birth weight, [1316] which is consistent with our present results. The newest ART surveillance in USA reported 23.6% infants conceived with ART were born low birth weight and 29.9% of ART infants were preterm.…”
Section: Discussionsupporting
confidence: 93%
“…Eighteen studies were matched cohorts, [17,19,22,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and sixteen unmatched cohorts. [18,20,21,[40][41][42][43][44][45][46][47][48][49][50][51][52] The quality of studies according to the NOS was moderate to high with NOS scores ranging from 4-9, of which 25 studies had scores of 8 or 9 ( Table 1). Publication bias was low as demonstrated by a funnel plot with symmetric distribution (Additional le 2, Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eight studies were matched cohorts, [17, 19, 27-29, 32, 35, 39] and six unmatched cohorts. [20,21,43,44,46,47] The quality of studies according to the NOS was moderate to high with NOS scores ranging from 6-9 (Table 1).…”
mentioning
confidence: 99%
“…In 14 studies, the indication for C-section was significant in pregnancies resulting from ART when compared with spontaneous pregnancies. [8][9][10]12,15,19,22,23,25,33,34,[38][39][40] -Premature and preterm rupture of membranes:…”
Section: Complicationsmentioning
confidence: 99%